TRADISI “PENGANTIN SAHUR" DI DESA PULAU PALAS KECAMATAN TEMBILAHAN HULU KABUPATEN INDRAGIRI HILIR - Uci Misdawati; Yusmar Yusuf (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Pengantin Sahur Tradition is a tradition of awakening citizens to live by parading several bridal couples whose brides are played by men and this tradition is held in Ramadan only. This tradition has been held since 1981 and developed until now. Informants from this research are the villagers of Pulau Palas. This study aims to determine the dynamics of the implementation of Pengantin Sahur and any factors that cause changes in the tradition of Pengantin Sahur. This research was conducted in Pulau Palas village, Tembilahan Hulu Subdistrict, Indragiri Hilir District. In this study used purposive techniques that determine the subject of research in accordance with certain criteria. The author communicates by using Banjar language, then the data is analyzed by qualitative method. In conducting the research, the authors found that Pengantin Sahur Tradition is vulnerable to experience changes on every year in the implementation process and appearance. Factors that cause this change are the innovations to make the Pengantin Sahur view more interesting, then also the increasingly dynamic society that always keep up with the times, and the change of village leaders where a leader determines how to develop the existing traditions and culture..Keywords: Pengantin Sahur, Tradition